PENGARUH GOOD CORPORATE GOVERNANCE (GCG) TERHADAP PROFITABILITAS DAN KINERJA SAHAM PERUSAHAAN PERBANKAN YANG TERCATAT DI BURSA EFEK INDONESIA - David Tjondro; Romanus Wilopo (Journal of Business & Banking, 2011)
GCG is interesting topic to be scrutinized. In this case, corporate governance system canprovide effective protection for stockholder and stakeholders, thus they can have confidencein return of investment. This study tries to analyze the impact of GCG toward profitabilityratios and bank stock performance. Samples of this study are banking companies listed inIndonesia Stock Exchange. Purposive sampling was used as sampling technique. Twenty sixcompanies were obtained by using several criterions as listed in IDX during 2008, no corporateaction which can change theoretical price in 2008 and complete data was available.GCG, ROA, ROE, NIM, stock return and PER was variable which studied in this research.Regression technique used to analyze the data. The research result shows that GCG havesignificant positive impact on ROA, ROE, NIM and PER. GCG doesnt have significant impacttoward stock return. It can be implied that investor access toward GCG implementationinformation in listed banking company must be widened and the capital market authoritiesshall conduct a regulation that forces public company to disclose GCG implementation